BOG IRON ORES IN CENTRAL CROATIA – MINERALOGICAL AND GEOLOGICAL CASE STUDY ON SOIL PROFILES - Tomislav Brenko; Sibila Borojević Šoštarić; Tena Karavidović; Tajana Sekelj Ivančan (Rudarsko-geološko-naftni Zbornik)
The Pokuplje and Posavina regions (central Croatia) offer unique insight into the environmental conditions that favour the formation of iron (Fe) ores in low-lying areas. Three soil profiles from Žakanje, Osekovo and Pravutine, located in the Kupa and Sava river plains, were analysed to understand their mineralogical and geochemical composition, with a focus on Fe enrichment and trace metal content. The presence of impermeable clay horizons in these profiles contributes to the formation of a redox boundary that favours the precipitation of Fe in the form of oxyhydroxides. The reddish mottling observed in the middle horizons suggests that the studied soils may represent an early stage of bog iron ore formation. Geochemical analysis shows that these soils are moderately to slightly acidic, with silt as the dominant granulometric fraction and variable Fe oxide content in the profiles. The high Fe concentrations are consistent with the depth of groundwater fluctuations, which must have driven the redox cycle and promoted mobility and deposition of Fe. The contents of several trace metals (Cr, Ni, Zn, Pb and As) showed correlation with Fe. This implies regional occurrences of siderite and Fe-containing hydrothermal zones as a possible source of Fe, transported and precipitated into soil via hydrological processes. Overall, the results suggest that the combination of clay-rich, flood-prone landscapes and seasonal groundwater fluctuations provide ideal conditions for the formation of bog iron ore in central Croatia. These types of ores could have been an economically viable source for iron production during archaeological periods.